Endogenous β-hydroxybutyrate and the risk of cognitive decline: a nested case-control study in the UK Biobank cohort - Eun, Youngmi; Newman, John C.; Lee, Ji Hyun; Kim, Se-Hong; Kim, Ha-Na (Frontiers in Aging Neuroscience, 2026)
Introductionβ-hydroxybutyrate (BHB) has been linked to improved cognitive function via enhanced cerebral metabolism and anti-inflammatory effects. However, evidence on the relationship between endogenous plasma BHB levels and cognitive decline remains limited. This study investigated whether higher plasma BHB levels are associated with reduced cognitive decline in middle-aged and older adults.MethodsWe conducted a nested case–control study within the UK Biobank prospective cohort. Among 4,653 participants with baseline plasma BHB measurements and cognitive assessments at baseline and follow-up, 2,143 cases of cognitive decline were matched to 2,143 controls by age, sex, and polygenic risk score for Alzheimer’s disease. Plasma BHB concentrations were measured by nuclear magnetic resonance spectroscopy. Cognitive function was assessed across five domains, and a global cognition score was derived through factor analysis. Cognitive decline was defined as a decrease in the global cognition score from baseline to follow-up. Conditional logistic regression and restricted cubic spline models were used to examine the associations between plasma BHB levels and cognitive decline, adjusting for demographic, lifestyle, and clinical factors.ResultsPlasma BHB concentrations were not significantly associated with global cognitive decline after covariate adjustment. However, higher plasma BHB tertiles were associated with a slower decline in fluid intelligence (adjusted OR for tertile 1 vs. 3, 0.83; 95% CI, 0.72–0.97).DiscussionEndogenous plasma BHB was not significantly associated with global cognitive decline but was inversely related to decline in fluid intelligence. Further studies are needed to clarify BHB’s role in cognitive aging.